Prophetic Studies of Multiculturalism: A Coloring Grace or A Potential for Gnawing Division - Agung Sulistiyo Nugroho; Musa Asy'arie; Mahasri Shobahiya (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
While contemporary studies on multiculturalism predominantly rely on secular political or educational frameworks, limited attention has been given to prophetic ethical paradigms as a systematic model for managing diversity. This study addresses this gap by examining multiculturalism in the era of the Prophet Muhammad SAW through a hermeneutical–prophetic approach grounded in Kuntowijoyo’s prophetic social science. Using qualitative library research, the study analyzes classical Islamic texts particularly the Medina Charteralongside relevant contemporary literature. The findings demonstrate that prophetic multiculturalism constitutes an ethical–political framework based on equality, religious freedom, social justice, and dialogical coexistence. Theoretically, this study reframes multiculturalism as a value-based moral system rather than a merely sociopolitical arrangement. Practically, it offers a normative reference for contemporary multicultural governance, education, and interfaith dialogue in plural societies facing increasing identity-based conflicts.